Peningkatan Budaya Keselamatan Pasien Melalui Peningkatan Motivasi Perawat dan Optimalisasi Peran Kepala Ruang - Mei Rani Wulandari; Sri Yulia; Renny Triwijayanti (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
A poor patient safety culture will have an impact on increasing the incident rateÂ or the risk of an incident. The patient safety culture is an important matter that needs to be considered by the hospital. The objectives of this research are finding out the relationship among nurse motivation, role of head nurse, and patient safety culture. This was a descriptive correlational study with cross sectional approach. The number of samples was 49 nurses. This study used chi-squareÂ test. Data were gathered by means of questionnaires about nurse motivation, role of head nurse, and patient safety culture. Results of this research describe 25 respondents (51%) had good motivation, 27 respondents (55.1%) had good role of head nurse, and 26 respondents (66.7) had good patient safety culture. The results showed that there was a relationship between nurse motivation and patient safety culture whith p value of 0.003 (p value < Î± 0,05) and there was a relationship between role of head nurse and patient safety culture with p value of 0.003 (p value < Î± 0,05). There was a relationship between nurse motivation and patient safety culture and there was a relationship between role of head nurse and patient safety culture. Nurseâ€™s motivation needs to be improved so that the quality of health workers is better and the efforts of the head nurse in carrying out his/her role in his/her unit need to be made more affective to optimize the patient safety culture.